2018
DOI: 10.1212/wnl.0000000000004761
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of neurofilaments in early symptom onset amyotrophic lateral sclerosis

Abstract: This study provides Class II evidence that CSF and serum Nf concentrations discriminate ALS with early symptom onset from other neurologic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
169
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(197 citation statements)
references
References 30 publications
21
169
6
1
Order By: Relevance
“…Correlations between neurofilaments and clinical parameters such as diagnostic latency and disease progression have been already been noted in previous studies in ALS [5, 6, 13, 14, 20]. We found that serum and CSF pNfH correlated significantly with progression rate at diagnosis and at the last observation, total ALSFRS-R score, and modified Rankin scale score at the last observation (albeit not at diagnosis).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Correlations between neurofilaments and clinical parameters such as diagnostic latency and disease progression have been already been noted in previous studies in ALS [5, 6, 13, 14, 20]. We found that serum and CSF pNfH correlated significantly with progression rate at diagnosis and at the last observation, total ALSFRS-R score, and modified Rankin scale score at the last observation (albeit not at diagnosis).…”
Section: Discussionsupporting
confidence: 86%
“…It is unknown whether the better diagnostic performance of serum NfL in their study was due to to a superior analytical outcome over pNfH or the larger sample size. Moreover, in our study biological samples were gathered at the time when patients sought medical attention because of disturbances due to UMN signs, which implies a shorter disease duration at the time of sampling compared to the abovementioned study, a fact which might have had an impact on neurofilament concentrations [5, 14]. Larger prospective studies comparing the the diagnostic performances of the 2 neurofilaments’ isoforms are therefore required to clarify which biomarker in serum is more functional for distinguishing between UMN syndromes at an early phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations